Hybrid Model of MSMEs for Livestock Hype Product Facing Consumer Sudden Shift on Pandemics - Kusumastuti, A.E; Putritamara, J. A; Azizah, S. (Technium Sustainability, 2021)
Pandemic covid-19 breakout has a massive impact on the MSMEs sector. The majority of producers could not survive due to unpreparedness to face the economic shock due to declining purchasing power. So that, the research was designed to create a resilient strategy for business through a hybrid model with an analysis of planned behavior theory. The research focuses on livestock products that currently excites the community, intended for role models of agricultural food products as perishable food and susceptible to an unbalanced market. So that, the decline in purchasing power of the consumers is imbalanced with availability and vice versa. The selected products are mozzarella cheese and honey. The research used an interview survey method with producers and consumers. Data analysis used game theory to design a model that conforms to the condition of the business. Results of the research showed that hybrid model of MSMEs for mozzarella and honey (livestock products which are hype during a pandemic) has the optimization of strategy to bring more adaptive business into reality by improvising strategy of popularity for mozzarella product of brand X and improvisation from an advocacy perspective for a honey product of MSMEs brand X. MSMEs products have opportunity to acquire market and compete with big companies in each product because it has superiority that would be able to meet the consumer needs and conform to the purchasing power.